Within and between day variability in temperate reef fish assemblages: Learned response to baited video - Birt, M.; Harvey, Euan; Langlois, T. (Elsevier, 2012)
Many studies that test for spatial patterns in fish assemblages do not have temporal replication, and where they do, the scale of this replication is in the order of seasons or years. Rarely are patterns tested at the scale of days or time of day. As a result, any descriptions of spatial patterns are potentially confounded by within or between day variations, with differences between locations possibly due to the differences between times sampled. This study aimed to determine whether significant short-term temporal variability existed within and between days in a temperate, shallow-water reef fish assemblage in south-western Australia. Three sites were sampled at morning, midday and afternoon for five consecutive days using baited remote underwater stereo–video systems. Significant differences were detected in the fish assemblage at different times of the day with morning and midday assemblages different from afternoon assemblages. Differences were detected between days with a significant shift in the assemblage after day two. The use of bait in this study was thought to influence the behaviour of Pseudocaranx spp. which furthermore influenced sampling of the entire fish assemblage between days. This study shows that large scale monitoring and sampling programmes using baited cameras need to consider the possible influence of within and between day variability in their experimental designs and must carefully design sampling to test for spatial and temporal structures in fish assemblages.